Exploring Young Learners’ Vocabulary Needs through Visual and Interactive Materials: A TEYL Perspective - St Hartina; Syahrir Syahrir; Fadhliyah Rahmah Muin (Universitas Islam Negeri Palopo, 2026)
This study investigated young EFL learners’ vocabulary learning needs in relation to visual and interactive materials. It addressed the question of what students need in vocabulary learning, what limitations they experience, and what types of vocabulary materials they prefer. The study used a convergent mixed-methods exploratory design with 20 young EFL learners and an English teacher at a public elementary school in Palopo, South Sulawesi. Quantitative data included a 12-item Likert-scale questionnaire addressing necessities, lacks, and wants, while qualitative data were generated via the semi-structured teacher interview protocol and several open-ended student responses. Descriptive statistics (means, percentages, and standard deviations) were used for quantitative data, and deductive and inductive thematic codes were used for qualitative data. The findings showed that students perceived vocabulary as necessary for understanding English textbooks (85%, M = 3.65), following teacher instructions (80%, M = 3.60), and producing simple English. They also reported difficulty retaining new vocabulary (70%, M = 3.45) and understanding words without pictures (65%, M = 3.35). Students preferred colorful pictures (90%, M = 3.80), daily-life topics (75%, M = 3.65), interactive activities (70%, M = 3.50), and manageable vocabulary loads (65%, M = 3.40). The results highlight the importance of visually, contextually, and interactively designed vocabulary material development that sufficiently integrates their needs, lacks, and wants.